Komensalitas dalam Batas: Modifikasi Aktivitas Makan Bersama di Masa Pandemi Covid-19 - Dhira Hanna Zakiyya (Umbara, 2022)
Commensality is the practice of people eating together and interact each other with their peer group to build social integration. Any restriction to carry out the practice of commensality can cause various problems stemming from the lack of a sense of relatedness and communal solidarity among the group members. The social restriction  since Covid-19 pandemic has changed people’s lives arrangement, including limiting the use of public spaces and all traditional activities involving commensality. This study examines the implications of social restriction policy on the practice of commensality in Banyuwangi and forms of adjustment and adaptation applied by the community in response to the policy. The study applied  qualitative descriptive method. Data was collected through in-depth interviews with sixteen informants. The results of the study suggests three forms of  adjustment dan adaptation applied by the community who practice commensality during social restriction, such as engaging in a new hobbies related to commensality, using a digital technology to improve the experience of commensality, and negotiation some ways in order to keep practicing the commensality.